Exploring the impact of mass migration in Jin Dynasty by psycholinguistic analysis on Classical Chinese legacy text - Xiong, Huan; Wu, Gengxuan; Li, Sijia; Xue, Shujie; Li, Hua; Zhu, Tingshao (Frontiers in Psychology, 2022)
The first mass migration in China took place at the end of the Western Jin, which resulted in the southward transfer of the Central Plains Culture and brought about huge social changes. Such social changes exerted significant impacts on the gentry of the Jin Dynasty. This paper used a huge volume of Classical Chinese legacy text of Jin gentry members. We used CC-LIWC to calculate frequencies of different word categories used in these text contents and conducted an analysis of variance to measure significant differences between the three groups. We found 16 categories of words with significant differences and calculated their effect sizes, such as tense markers (tensem), F=3.588, P<0.05, η2=.034; modal particles (modal_pa), F=3.468, P<0.05, η2=.053; words for affective processes (affect), F=3.096, P<0.05, η2=.028; words for cognitive processes (cogproc), F=3.308, P<0.05, η2=.031; words for perceptual processes (percept), F=7.137, P<0.05, η2=.06. Combining the psycholinguistics of the 16 categories of words and researches of historians on the Jin Dynasty, we then analyzed the direct and indirect, immediate and long-lasting psycholinguistic impacts of this mass migration on the gentry themselves and their descendants.